Effect of CMC Concentration from Oil Palm Empty Fruit Bunches and Tapioca Starch Ratio on Biodegradable Adhesive Properties - Elnis Seftiani Gaho; M. Prasanto Bimantio (G-Tech: Jurnal Teknologi Terapan, 2026)
This study examines the use of empty oil palm bunch waste (EFB) as a raw material for Carboxymethyl Cellulose (CMC) for the development of biomass-based biodegradable adhesive. The novelty of this research lies in the application of EFB-derived CMC combined with tapioca starch as a biodegradable adhesive system that remains underexplored in bioadhesive development. The study used a randomized complete block design of two factors, namely the concentration of CMC (1%, 2%, and 3%) and the ratio of tapioca starch (6 g, 12 g, and 18 g). The parameters tested include viscosity, pH, adhesion, and drying time. The results showed that the concentration of CMC and tapioca starch had a significant effect on viscosity, adhesion, and sdrying time, but had no effect on pH. Increasing tapioca starch and CMC concentrations increased viscosity and adhesion through the formation of amylose–amylopectin gel network and hydrogen bond interactions with CMC, but slow down drying time due to increased water retention in the gel matrixThe best treatment was obtained in the C3P3 combination which produces the highest viscosity and adhesion values. This study confirms that EFB has the potential to be used as a raw material for CMC to produce biodegradable adhesive that is more environmentally friendly than synthetic adhesives and provides added value to palm oil industry waste.